TAK ADE: Tutur Bahasa Basa-Basi pada Orang Melayu di Pulau Penyengat, Kota Tanjungpinang - Utami, Fathya Tyas Yudila; Meiyenti, Sri; Yunarti, Yunarti (Umbara, 2024)
Small talk serves as a societal effort to foster interactions among individuals. This linguistic habit plays a vital role in maintaining the stability of social interactions. A similar phenomenon is observed in Pulau Penyengat, where small talk is deeply ingrained in the community's daily life. Instead of using the conventional phrase "how are you," the people of Pulau Penyengat employ a unique term, "tak ade". This term opens a window into understanding the patterns of small talk and its significance in the lives of the island's residents. This qualitative study employs an ethnographic approach. Data were collected through observation, in-depth interviews, and literature review. The analysis involved three stages: data reduction, triangulation, and verification or conclusion drawing. The findings reveal four distinct patterns of small talk in Pulau Penyengat: speech context, actor patterns, pronunciation patterns, and the usage patterns of "tak ade". Additionally, the research identifies a categorization of community groups based on how they interpret "tak ade" in their small talk habits. These groups consist of the noble Melayu and the commoner Melayu.